Konsep Keadilan dalam Alquran - Muhyidin, Syaiful (Al-Riwayah : Jurnal Kependidikan, 2019)
This paper discusses the concept of justice contained in the Qur'an. Allah Almighty as the "Most Just" (al-Adlu) has required the implementation of justice principles for humans. The study of justice is one of the central themes in intellectual studies and Islamic studies such as fiqh and hadith. In its discussion, justice is conveyed in two terms namely al-'adl and al-qisthu which both have identical textual meanings but there are differences in several aspects. The concept of justice is divided into 4 concepts, namely: fair in the sense of being equal, fair in the sense of being balanced, fair in the sense of considering and fulfilling one's rights, and fair in the sense attributed to Allah. The fundamental difference in the meaning of justice lies in the contextual aspects (legal issues and measurements). Furthermore, justice is someone's right distribution that have been agreed without any special tendency to certain parties. In its continuation, the application of justice can be formulated as welfare